2017
DOI: 10.1101/204578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diffusional conductance to CO2 is the key limitation to photosynthesis in salt-stressed leaves of rice (Oryza sativa)

Abstract: Salinity significantly limits leaf photosynthesis but the photosynthetic limiting factors in salt- stressed leaves remain unclear. In the present work, photosynthetic and biochemical traits were investigated in four rice genotypes under two NaCl (0 and 150 mM) concentration to assess the stomatal, mesophyll and biochemical contributions to reduced photosynthetic rate (A) in salt stressed leaves. Our results indicated that salinity led to a decrease in A, leaf osmotic potential, electron transport rate and CO2 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 58 publications
3
10
0
Order By: Relevance
“…where, Φ PSII is the actual photochemical efficiency of photosystem II, α is the leaf absorptivity and β is the partitioning of absorbed quanta between photosystems II and I. In the current study, the αβ value of 0.44 was used based on the previous studies [38,41].…”
Section: Gas Exchange Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…where, Φ PSII is the actual photochemical efficiency of photosystem II, α is the leaf absorptivity and β is the partitioning of absorbed quanta between photosystems II and I. In the current study, the αβ value of 0.44 was used based on the previous studies [38,41].…”
Section: Gas Exchange Measurementsmentioning
confidence: 99%
“…where A is the photosynthetic rate at PPFD of 1500 μmol m −2 s −1 , C i is the CO 2 mol fraction in the intercellular air space, Γ * represents the CO 2 compensation point in the absence of mitochondrial respiration and R d is the daytime respiration rate. Typical values of 40 μmol mol −1 and 1 μmol m −2 s −1 were used for Γ * and R d , respectively [38]. For each data point generated, we checked whether it met the criterion (10 > dC c /dA > 50) [14].…”
Section: Gas Exchange Measurementsmentioning
confidence: 99%
“…The effects of C i and light on g m in a LSM have so far only been tested once by adding empirical response functions to Equation (6) (Figure d,e; Knauer et al , ). Other factors such as salt stress (Delfine et al , ; Wang et al , ) and ozone (Xu et al , ) have been reported to negatively affect g m instantaneously, but these stressors are not always considered in LSMs and have not yet been investigated with respect to g m . On longer time scales (weeks to years) g m is affected by nutrient availability (Jin et al , ; Yamori et al , ) and leaf age (Warren, ; Yin et al , ).…”
Section: Implementation Of Mesophyll Conductance Into Lsmsmentioning
confidence: 99%
“…Photosynthesis is the key physiological process of plants and can provide 90% of plant biomass (Wang et al 2018). Leaves are the main contributors to the crop productivity (Ashraf and Bashir 2003), and their photosynthetic activities are crucial significantly for harvestable fruit yield.…”
Section: Introductionmentioning
confidence: 99%